2017
DOI: 10.1155/2017/2060549
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy of Yindanxinnaotong Soft Capsule in the Treatment of Stroke and Angina Pectoris: A Meta‐Analysis

Abstract: Objective. To systematically evaluate the clinical efficacy of Yindanxinnaotong (YD) soft capsule in adult patients with cardiovascular diseases (stroke and angina pectoris). Methods. We electronically searched databases including Medline, PubMed, Chinese National Knowledge Infrastructure (CNKI), Cqvip Database (VIP), and Wanfang Database for published articles of randomized controlled trials (RCTs) of YD capsule in treating stroke and angina pectoris. The meta-analysis was performed using RevMan 5.3 software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In case of disagreement, it will be approved by a third researcher. The extracted contents include the type of study design, baseline characteristics, intervention methods (intervention measures and treatment duration), leading outcome indicators, and adverse reactions [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…In case of disagreement, it will be approved by a third researcher. The extracted contents include the type of study design, baseline characteristics, intervention methods (intervention measures and treatment duration), leading outcome indicators, and adverse reactions [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the routine treatment of WM, the combination of Shexiang Baoxin pills [33][34][35] or Yindan Xinnaotong soft capsule [36] can decrease IMR. A Meta-Analysis analysis results demonstrated that Yindanxinnaotong soft capsule could regulate coagulation condition and fibrinolytic system in patients with CAD and improve myocardial ischemia, angina symptoms, and heart function, reduce restenosis after PCI, and regulate blood lipids, control the long-term development of the cardiovascular disease and prevent the cardiovascular events from happening again [37]. Shexiang Baoxin pills [38] or Xuefu Zhuyu capsule [39] combined with routine WM can prolong the duration of treadmill exercise in patients with microvascular angina.…”
Section: Qi Stagnation and Blood Stasis Syndromementioning
confidence: 99%
“…The clari cation of bioactive components is a fundamental step to explain the mechanism of TCMs [2]. Yindan Xinnaotong soft capsule (YDXNT), composed of eight crude drugs including Ginkgo Folium (Yinxingye), Salviae Miltiorrhizae Radix et Rhizoma (Danshen), Erigerontis Herba (Dengzhanxixin), Crataegi Fructus (Shanzha), Notoginseng Radix et Rhizoma (Sanqi), Gynostemmatis Herba (Jiaogulan), Allii Sativi Bulbus (Dasuan) and L-borneolum (Aipian) is an herbal prescription for clinical treatment of cardiovascular diseases (CVD) [3]. Among them, Ginkgo Folium, Salviae Miltiorrhizae Radix et Rhizoma, and Notoginseng Radix et Rhizoma are the frequently used drugs in the CVD-treating TCM formula [4][5][6].…”
Section: Introductionmentioning
confidence: 99%